Environmental and Management Factor Contributions to Maize Yield - Frederick E. Below (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Agricultural production must increase substantially to meet the increasing per capita demand for food, feed, fuel, and fiber of a rising human census. The amount of arable land is limited due to soil type, weather, and ecosystem considerations; therefore, it is necessary to increase yields on current fields. To obtain the greatest maize (Zea mays L.) yield, a farmer needs to nurture the crop as much as possible. Weather and nitrogen availability are well- known as two factors that normally have the greatest influence on maize yields and grain quality. Some management factors a producer may need to consider while growing a maize crop are mineral fertilization, genotype, plant population, and protection from insects and diseases. Additionally, there are numerous biological and chemical compounds that can stimulate plant growth, such as in-furrow mixes and foliar fungicides. Field management also plays a role in final grain yield, including crop rotation, tillage, soil pH and nutrient levels, weed control, and drainage. This Special Issue Book focuses on weather, soil, and other maize crop management factors and their relative independent and/or interactive influence on maize growth and yield.]